Poverty reduction through vocational and technical education among graduates in Oyo State, Nigeria - Salami, Sarafadeen Segun; Afolabi, Oluwatunmise (International Journal on Education Insight, 2022)
Poverty and unemployment especially among the graduates has remained major challenges threating the economic growth and development of Nigeria. Towards poverty reduction Vocational and technical education is imperative. Therefore, this study examined poverty reduction through vocational and technical education among graduates in Oyo State, Nigeria. Four (4) research questions guided the study. The study adopted descriptive survey design. A total of 390 vocational and technical education students formed the sample size of the study out of 3,900 graduates. A structured questionnaire developed by the researchers tagged: Poverty Reduction through Vocational and Technical Education Questionnaire (PRVTEQ) validated by three (3) experts was used for the study. Split half method was used to established reliability coefficient and the overall reliability coefficient was also established at 0.87 using Cronbach Alpha. The data generated for the study were analysed using mean and standard deviation. The findings showed among others that vocational and technical education increase pace for technological innovations, improve citizens standard of living, facilitate social Economy growth and development and promote political stability. Based on the findings the researcher recommended among others, government through its agencies should map out strategies of reaching out and providing funds for individuals who are willing to set up businesses and that school management should provide more vocational centers for skills acquisition towards poverty reduction.